Bridge over rapids below Deep Lake, White Pass Trail, British Columbia, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "Rapids below Deep Lake. For packtrains only. Skagway Trail" Original image in Hegg Album 9, page 16. Klondike Gold Rush.